ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN DANA PEMINJAMAN KREDIT BRI (Studi Kasus: Karyawan PTPNIII Kebun Rambutan) - Rotua Lusianna Manurung (Ekonomi dan Keuangan, 2014)
Economic growth has affected the higher-level needs. Loan funds are part of employees in an effort to help meet the needs. The purpose of this study is to analyze the factors that affect the using of the loan funds from income, education level, number of dependents and long term employeer working at PTPNIII Kebun Rambutan. The data’s used in this analysis is the primary data on directly observation at officer PTPNIII Kebun Rambutan. Determination of the sample using a snowball sampling method. The samples in this study are employers who earn PTPNIII Kebun Rambutan BRI loan fund as many as 31 employers. Tests using statistical data processing software is SPSS 19. To look at the factors that effects the using of loan funds use multiple linear regression analysis tools and paried sample T-test. Results of multiple linear regression analysis in this study show that income, education levels and long term employers working positively influence to the using of loan funds, and the other side the number of dependents negatively affect the using of loan funds. And the results of analysis of samples paried T Test show a significant difference between before doing loan and income after doing loan. Those factors which may affect the using of loan funds of BRI employers at PTPNIII Kebun Rambutan.Keyword: Income, Education Level, Number of Dependents, Old Working, Total Loans, Multiple Linear Regression, Paried Samples T-Test.